Citrus aurantium L. peel extract mitigates hexavalent chromium-induced oxidative stress and cardiotoxicity in adult rats - Mariem Chaabane; Awatef Elwej; Imen Ghorbel; Tahia Boudawara; Najiba Zeghal; Nejla Soudani (Mazandaran University of Medical Sciences, 2017)
In the present study, we aimed to examine the potential protective effect of C. aurantinum L. peel extract against oxidative damage induced by hexavalent chromium in the heart of adult rats. Rats were divided into six groups. Group I served as controls and received standard diet. Group II received via drinking water potassium dichromate (K2Cr2O7) alone (700 ppm) during 3 weeks. Groups III and IV were pre-treated for 10 days by gavage with the ethanolic extract of C. aurantium peels at doses of 100 and 300 mg/kg body weight/day, respectively, and then K2Cr2O7 was administrated during 3 weeks. Groups V and VI received by gavage only C. aurantium peel ethanolic extract at doses of 100 and 300 mg/kg body weight/day, respectively, during 10 days. K2Cr2O7 treatment increased the cardiac levels of malondialdehyde (MDA), protein carbonyls (PCO), advanced oxidation protein products (AOPP), non-protein thiols, glutathione and vitamin C, as well as the activities of catalase, superoxide dismutase and glutathione peroxidase. Cardiac histological alterations, manifested by hemorrhage and cytoplasmic vacuolization, were also observed. Pre-treatment with C. aurantium peel extract (300 mg/kg) attenuated significantly the biochemical and histopathological changes observed following K2Cr2O7 exposure in rat’s heart. Our findings indicated that C. aurantium peel extract was able to hamper K2Cr2O7-induced myocardial injury, which could be attributed to its antioxidant activity.